2006
DOI: 10.1111/j.1365-2672.2006.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Human astroviruses in raw sewage samples in Hungary

Abstract: Aims:  Routine procedures for monitoring viruses in water samples have not been drawn up for the water‐microbiology screening panel. Enteric viruses, including astroviruses, are able to persist under environmental conditions and may cause public health problems by contaminating natural and drinking water resources. The aim of this study was to detect human astroviruses (HAstVs) from raw wastewater samples. Methods and Results:  To obtain data on whether human astroviruses are shed in the environment, 35 raw se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…A similar study in Norway, however, reported a higher prevalence of astrovirus in raw sewage of 46-94% (Myrmel et al 2006). A study on astrovirus in Hungary also showed a relatively high prevalence (43%) (Meleg et al 2006). Tajima et al (2007) reported that norovirus was detected in 20 of 22 specimens (91%) in the secondary effluent and 20 of 28 specimens (71%) in the reclaimed water after tertiary treatments.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A similar study in Norway, however, reported a higher prevalence of astrovirus in raw sewage of 46-94% (Myrmel et al 2006). A study on astrovirus in Hungary also showed a relatively high prevalence (43%) (Meleg et al 2006). Tajima et al (2007) reported that norovirus was detected in 20 of 22 specimens (91%) in the secondary effluent and 20 of 28 specimens (71%) in the reclaimed water after tertiary treatments.…”
Section: Discussionmentioning
confidence: 95%
“…(Meleg et al 2006;Rutjes et al 2009). Outbreaks of viral acute gastroenteritis by consumption of contaminated water have been frequently reported in the world, and viruses are known as the etiological agents for the infectious gastroenteritis (Divizia et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Beijing, the treated water, regarded as a second water source, has been used as toilet flushing water, industrial process water, environmental water, garden water, and road washing water (He et al 2008). Sewage treatment and disinfective procedures for wastewater have only a limited effect on a number of viruses, and therefore treated sewage water still contain enteric viruses (Meleg et al 2006;He et al 2011). Because of discharges of treated sewage, pathogenic microorganisms may enter surface waters in Beijing, and therefore viruses are able to contam-inate environmental waters thus preserving a longterm capacity for infection.…”
Section: Introductionmentioning
confidence: 99%